Livers provide a reliable matrix for real-time PCR confirmation of avian botulism. (April 2016) - Le Maréchal, Caroline; Ballan, Valentine; Rouxel, Sandra; Bayon-Auboyer, Marie-Hélène; Baudouard, Marie-Agnès; Morvan, Hervé; Houard, Emmanuelle; Poëzevara, Typhaine; Souillard, Rozenn; Woudstra, Cédric; Le Bouquin, Sophie; Fach, Patrick; et al.
Abstract: Diagnosis of avian botulism is based on clinical symptoms, which are indicative but not specific. Laboratory investigations are therefore required to confirm clinical suspicions and establish a definitive diagnosis. Real-time PCR methods have recently been developed for the detection of Clostridium botulinum group III producing type C, D, C/D or D/C toxins. However, no study has been conducted to determine which types of matrices should be analyzed for laboratory confirmation using this approach. This study reports on the comparison of different matrices (pooled intestinal contents, livers, spleens and cloacal swabs) for PCR detection of C. botulinum . Between 2013 and 2015, 63 avian botulism suspicions were tested and 37 were confirmed as botulism. Analysis of livers using real-time PCR after enrichment led to the confirmation of 97% of the botulism outbreaks. Using the same method, spleens led to the confirmation of 90% of botulism outbreaks, cloacal swabs of 93% and pooled intestinal contents of 46%. Liver appears to be the most reliable type of matrix for laboratory confirmation using real-time PCR analysis. Highlights: 63 suspicions of avian botulism were investigated for laboratory confirmation. Detection of Clostridium botulinum type C, D, C/D, D/C, E was performed using Real-time PCR. Spleens, livers, cloacal swabs, pooled intestinal contents were used as matrices. Livers allowed the best rate confirmation (97%) using real-time PCR.